2023
DOI: 10.1021/acsenergylett.2c02683
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking the Safety Performance of Organic Electrolytes for Rechargeable Lithium Batteries: A Thermochemical Perspective

Abstract: Developing nonflammable organic electrolytes has been regarded as one of the most valuable strategies for tackling the safety issues of rechargeable lithium batteries. However, a quantitative and precise evaluation of electrolyte safety remains challenging mostly because of the inconsistent measurement conditions and the lack of a basic reference system. In this work, we performed a benchmark study on the safety of organic electrolytes by characterizing with cone calorimetry the thermochemistry of various type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 46 publications
(56 reference statements)
0
22
0
Order By: Relevance
“…It collects thermophysical constants of materials including SET, total heat release (THR), maximum heat release rate (MHRR) and time to ignition (TTI) and is more accurate than manual SET testing. Yang et al 41 employed a cone calorimeter to compare the flammability of eight single solvent electrolytes and found that a combination of nonflammable polyfluorinated solvents and high boiling point solvents was the optimal choice for nonflammable electrolyte design with low THR, low MHRR, long TTI and short SET.…”
Section: Thermal Failure In Libsmentioning
confidence: 99%
“…It collects thermophysical constants of materials including SET, total heat release (THR), maximum heat release rate (MHRR) and time to ignition (TTI) and is more accurate than manual SET testing. Yang et al 41 employed a cone calorimeter to compare the flammability of eight single solvent electrolytes and found that a combination of nonflammable polyfluorinated solvents and high boiling point solvents was the optimal choice for nonflammable electrolyte design with low THR, low MHRR, long TTI and short SET.…”
Section: Thermal Failure In Libsmentioning
confidence: 99%
“…[1][2][3][4] As a result, various strategies have been successfully employed to suppress dendritic lithium growth in lithium-metal batteries (LMBs), [5][6][7][8] which is one of the critical causes that could occur safety issues. [9][10][11][12] In particular, carbon-based materials have shown great potential as lithium host materials. A diverse range of carbon materials such as graphene, carbon nanotubes (CNTs), carbon nanobers (CNFs), and carbon spheres have been used to effectively accommodate lithium due to their high conductivity, lithiophilicity, chemical/physical stability, and low gravimetric density.…”
Section: Introductionmentioning
confidence: 99%
“…So, the stability of LMA plays a crucial role in the safety of lithium metal batteries (LMBs). 16,17 Various strategies have been made to modify the Cu substrate, such as high-temperature calcination, 18 spin coating, 19 chemical vapor deposition, 20 and electrospinning. However, most of these methods require complex design and material synthesis procedures, which will increase the complexity of the LMA fabrication process, while, in some cases, the large addition of inactive substances will reduce the energy density of the LMBs.…”
Section: Introductionmentioning
confidence: 99%
“…Severe dendrite growth and poor cycling stability will exist for Cu-hosted LMA, which will finally lead to battery short circuit, thermal runaway, , and even explosion or fire. So, the stability of LMA plays a crucial role in the safety of lithium metal batteries (LMBs). , …”
Section: Introductionmentioning
confidence: 99%